The changes in glycemic control and cardiovascular risks among type 2 diabetes mellitus patients in Kelantan enhanced primary healthcare clinics pre and post-covid-19 pandemic - Sukeri, Nur Hafizah (2023)
Background: Type 2 Diabetes Mellitus (T2DM) is a significant health concern and has reached alarming levels. Diabetes patients are two to three times more likely to develop cardiovascular disease and die prematurely than non-diabetics. COVID-19 pandemic has affected lifestyle and healthcare access to patient and exacerbated this challenging situation. Objective: To study the changes in glycemic control and cardiovascular risk pre and post-pandemic COVID-19 and associated factors of uncontrolled post-pandemic glycemic status among T2DM patients at Kelantan EnPHC clinics. Methodology: This was a cross-sectional secondary data review, conducted from 14 March 2023 till June 2023. Two hundred and fifty data of Type 2 Diabetes Mellitus patients were acquired from patients’ medical records. Descriptive and multiple logistic regression analysis were performed using IBM SPSS Statistics version 27 software. Result: The mean age was 64.7 (10.40). The majority of patients were Malay [236 (94.4 %)], female [187 (74.8%)], married [149 (59.6%)], unemployed which is housewives [129 (66.2%)] and [79 (47.6%)] patients received secondary education followed by primary education [50 (30.1%)]. Ninety-five percent of the patients have underlying comorbidities and the highest comorbidities were hypertension [215 (86.0%)] and hyperlipidemia [203 (81.2%)]. Nephropathy [72(28.8%)] was the highest diabetic complication followed by retinopathy [40 (16%)]. There were 182 (72.8%) patients with uncontrolled glycemia post-pandemic COVID-19 respectively. Patient with uncontrolled glycemia pre-pandemic COVID-19 has 16.03 times the odds to have uncontrolled glycemia post-pandemic COVID-19 compared to patient with controlled glycemia pre-pandemic when adjusted for total cholesterol level pre-pandemic COVID-19 (16.03 (8.11, 31.70), p-value <0.001). Patient with an increase in 1 mmol/l of total cholesterol level pre-pandemic has 1.36 times the odds to have uncontrolled glycemia post-pandemic (95% CI: 1.020 to 1.806, p-value <0.05) when adjusted for uncontrol glycemic pre-pandemic COVID-19. Conclusion: The pandemic restrictive measures do not affect glycemic control as well as other cardiovascular risks. Individual patient factor on self-management is important to ensure the continuation of good glycemic control despite changes in healthcare services due to the pandemic. Enhancing the implementation of a chronic care model (CCM) for chronic disease management and telemedicine is a good alternative for patient monitoring, health education, consultation, and psychosocial support especially during a pandemic or disaster situation.